Identification of Research gaps on Municipal Solid Waste Management from Data Indexed in the SCOPUS Database - Espuny, Maximilian [UNESP]; Reis, Jose Salvador da Motta; Anaya, Yadirka Bolano [UNESP]; Cardoso, Ronald Palandi; Sampaio, Nilo Antonio de Souza; Barbosa, Luis Cesar Ferreira Motta; Oliveira, Otavio Jose de [UNESP] (Sindicato Secretarias Estado Sao Paulo, 2022)
This study aimed to identify the research gaps on the theme Municipal Solid Waste Management, as from the analysis of articles indexed in the SCOPUS database. For this objective to be achieved, an applied research of exploratory nature and qualitative approach was carried out. It is noteworthy that, as method and technical procedures were adopted, respectively, the bibliographic research and the literature review. The data used in the analysis were obtained from the SCOPUS database in May 2018 and treated using Microsoft Excel (R) software. It is noteworthy that as a selection criterion, thirty papers indexed in this base that presented the highest number of citations were analyzed. As main results, it can be highlighted that the identified gaps were grouped into eight categories. Among the categories analyzed, one can highlight life cycle assessment, with ten gaps, and tools for municipal solid waste management, with eight. It is also noteworthy that the category municipal solid waste management associated with other methodologies occupies the second position, along with tools for the management of municipal solid waste, indicating the lack of studies in the highlighted areas and pointing out the relevance of the theme for the academic environ.
Keywords: Municipal Solid Waste Management; Solid Waste; SWM; SCOPUS Bibliometrics